Neglected endings : the significance of the Pauline letter closings - Weima, Jeffrey A. D. (Journal for the study of the New Testament. Supplement series, 1994)
Biblical commentaries generally treat the Pauline letter closings in a cursory manner and are typically at a loss to explain how a particular closing section relates in any meaningful way to the rest of the letter. In this ground-breaking study the author aims to rectify the imbalance that exists in the epistolary analysis of Paul's letters by providing a comprehensive, detailed study of his letter closings. By first surveying the history of epistolary analysis and examining the conventions used in ancient Hellenistic and Semitic letters, the author's examination of the Pauline epistles reveal.